1997
DOI: 10.1258/002367797780596239
|View full text |Cite
|
Sign up to set email alerts
|

Portacaval shunt control animals: physiological consequences derived from the sham operation

Abstract: SummaryThe portacaval shunt in the rat is a frequently used experimental model of porto systemic encephalopathy. Among other consequences of this surgical preparation is an important decrease in hepatic and testicular volume. Different sham-operation methods including a laparotomy were used as controls in each case. Given that the liver volume varies greatly in comparison to body weight in the sham-operated animals, this paper aims to evaluate the possible consequences of the sham operation. It concludes that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…To study these portacaval shunt experimental models, sham-operated rats are usually used as a control. The sham operation consists of portal vein clamping during a similar period of time to that of the portacaval shunt [57] .…”
Section: Portacaval Shuntsmentioning
confidence: 99%
“…To study these portacaval shunt experimental models, sham-operated rats are usually used as a control. The sham operation consists of portal vein clamping during a similar period of time to that of the portacaval shunt [57] .…”
Section: Portacaval Shuntsmentioning
confidence: 99%
“…Decrease in the relative weight of the testis for each 100 g of body weight has been also described in rats with a portocaval shunt, although in these cases the body-weight increase positively correlates to lower testicular atrophy [19]. The body-weight increase with hepatomegaly in SPVS as well as in TPVS rats suggests the existence of liver steatosis associated to obesity [20,21].…”
Section: New Methodologiesmentioning
confidence: 82%
“…Also, at 60 days of evolution after clamping of portal vein for 15 min and clamping of portal vein for 5 min in rats, a decrease in the relative weight of the testis for each 100 g of body weight has also been found [19]. These results make it possible to hypothesize that both acute and chronic alterations secondary to portal hypertension could re ect the existence of a long-term systemic response, which would also be heterogeneous, especially in chronic portal hypertension.…”
Section: New Methodologiesmentioning
confidence: 89%
“…Both factors could be involved in the production of bacterial translocation at 48 h of postoperative evolution in SO rats, although they could also pathologically affect the intestinal permeability in the long term. We have previously found that the temporal portal clamp (5-15 min) of the portal vein in the rat reduces body, testicular and hepatic weights, and continues at 60 days of postoperative evolution [61].…”
Section: Discussionmentioning
confidence: 98%